Sports Massage for School Drops and Orphans - Gede Hendri Ari Susila (International Journal of Community Service Learning, 2026)
This community service activity was carried out due to the increasing number of orphans, underprivileged children, and dropouts among teenagers. This activity aims to empower the community in sports and health while opening alternative economic opportunities for socio-economically vulnerable groups, through the Competitive Community Service for Beginners program from the Ministry of Religion. The activity was carried out through lectures, demonstrations, question-and-answer sessions, and direct practice. At the end of the activity, a final evaluation was held. This evaluation was based on all participants' activities during the training. 8 participants attended the training. The results of this training made children able to improve their sports massage technique skills, which include Effleurage (rubbing movements), Petrissage (massage movements), Friction (grinding movements), Shaking (shaking movements), Tapotement (hitting movements), Vibration (vibrating movements), and Stroking (massage movements). This community service activity was successful, with 100% of participants attending and practicing all techniques. The sports massage implementers collaborate with the Village Government and the Manpower Office (Disnaker) to facilitate the sustainability of sports massage skills in the world of work. The implications of this sports massage training can develop the skills of orphans and school dropouts, enabling them to compete in the world of work.